Relationship between Demographic Characteristics and Patients' Satisfaction with TU Teaching Hospital's Services (International Journal of Atharva, 2023)
The aim of this study was to explore the relationship between demographic characteristics and patients’ trust in doctors. To reach the goal of the study research, a cross-sectional time horizon and descriptive study method were used. Results revealed a significant relationship between age and patient satisfaction regarding trust at TU Teaching Hospital in Kathmandu, Nepal. This indicates that patients of various age groups expressed different levels of trust in the hospital. Additionally, the analysis also indicated a significant relationship between gender and patient satisfaction regarding trust at the same hospital. However, there was no significant relationship found between the number of visit times and patient satisfaction regarding trust. These findings imply that age and gender play a role in shaping patients' trust levels, while the frequency of visits does not significantly impact patient satisfaction with trust at TU Teaching Hospital. As a renowned hospital, TU Teaching Hospital in Kathmandu, Nepal enjoys higher levels of trust from patients who visit from different districts across Nepal.